Presenting Examples in Learners’ Dictionaries to Assist Chinese Learners in Writing English Texts - Xue, Mei (HERMES - Journal of Language and Communication in Business, 2011)
It has been widely acknowledged that exempliﬁcation plays a very signiﬁcant role in foreign language learning. Many studies have been conducted on dictionary examples, but little attention has been paid to how examples can assist a speciﬁc group of foreign learners engaged in a speciﬁc learning activity. The present study is intended to ﬁll this gap by investigating how to optimize examples in English learners’ dictionaries to help Chinese learners with writing in English. The functional theory of lexicography will be employed in this study. This investigation will be carried out in two stages. The ﬁrst one consists in identifying the lexicographic needs of foreign learners engaged in the task of English writing and consulting dictionary examples. The second stage is a demonstration of some proposals for exempliﬁcation in learners’ dictionaries through model articles. The purpose of this study is to give new insights into exempliﬁcation in learners’ dictionaries for future lexicographic research and practice.